2006
DOI: 10.1161/circulationaha.106.620476
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary ST-Segment Shift Soon After Elective Percutaneous Coronary Intervention Accurately Predicts Periprocedural Myocardial Injury

Abstract: Background-Elevation of cardiac biomarkers after coronary angioplasty (percutaneous coronary intervention [PCI])reflects periprocedural myocardial damage and is associated with adverse cardiac events. We assessed whether periprocedural myocardial damage that occurs despite successful PCI could be rapidly and easily identified by intracoronary ST-segment recording with the use of a catheter guidewire. Methods and Results-In 108 consecutive stable patients undergoing elective single-vessel PCI, we recorded unipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 30 publications
(24 reference statements)
1
39
0
2
Order By: Relevance
“…The present method is more comprehensive, however, as it provides a base for demonstrating the exact zone location source of possible troponin rise after intervention. In the subgroup of our patients with undetectable baseline troponin values, as in the cited studies, we demonstrated higher sensitivity and better negative predictive value (100%) in comparison with previous studies, with a slightly lower specificity (91% in our study vs. 95% in the Balian et al [8] study and 92% in the study by Uetani et al [10]). Since a different distribution of icECG shifts exists in the MB, this may explain the different sensitivity and specificity detected in previous studies.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…The present method is more comprehensive, however, as it provides a base for demonstrating the exact zone location source of possible troponin rise after intervention. In the subgroup of our patients with undetectable baseline troponin values, as in the cited studies, we demonstrated higher sensitivity and better negative predictive value (100%) in comparison with previous studies, with a slightly lower specificity (91% in our study vs. 95% in the Balian et al [8] study and 92% in the study by Uetani et al [10]). Since a different distribution of icECG shifts exists in the MB, this may explain the different sensitivity and specificity detected in previous studies.…”
Section: Discussionsupporting
confidence: 73%
“…Our results are comparable with the results of previous studies performed in non-bifurcation coronary interventions. Balian et al [8], in group of 108 stable, low-risk, non-bifurcation coronary patient population, found 74% sensitivity, 95% specificity, and 93% and 81% PPV and NPV, respectively, for any troponin increase. Despite the lower risk patient cohort, the frequency of postprocedural enzyme increase was almost identical to our patient population, although no data were provided about sensitivity and specificity of method regarding > 5 × N troponin I increase.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations